ANALYSIS OF PLASTIC WASTE MANAGEMENT AND ITS IMPLICATIONS FOR COMMUNITY ECONOMIC ACTIVITIES IN THE MARDIKA MARKET AREA, AMBON CITY - Sitra Yani Belasa; Marannu Paledung; Sheilla Vilensia Tijahahu; Dean Marchia Unawekla; Rosdiana Yudith Mantouw; Feliks Jhonrey Salamor; Wahyu Malik; Shean Juan Rompas; Nurlina Belasa (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
Plastic waste is an environmental problem that continues to increase along with the development of community economic activities, especially in traditional market areas. Mardika Market, Ambon City, as a center of trade and community economic activities, produces a fairly high volume of plastic waste, requiring effective and sustainable management. This study aims to analyze plastic waste management and its implications for community economic activities in the Mardika Market area of ​​Ambon City. The study used a qualitative descriptive method with a literature study and document analysis approach. Data were obtained from publications from the Central Statistics Agency (BPS), the National Waste Management Information System (SIPSN), scientific journals, government reports, and various relevant documents. Data analysis was carried out through the stages of data collection, data reduction, data presentation, and drawing conclusions. The results of the study indicate that plastic waste management in the Mardika Market area still faces various challenges, including the high use of single-use plastics, limited community participation, and the suboptimal implementation of the Reduce, Reuse, and Recycle (3R) principles. These conditions have implications for the cleanliness and comfort of the market environment, which can affect community economic activities, especially visitor comfort and trading activities. Therefore, synergy between the government, traders, and the community is needed to improve the effectiveness of plastic waste management to support the creation of a clean, comfortable, and productive market environment.